Unusual presentation of Crohn disease associated with hemophagocytic lymphohistiocytosis syndrome: a case report - Cuadros Mendoza, Carlos Augusto (2025)
Crohn’s disease (CD) is a chronic, multifactorial inflammatory condition that can affect any part of the gastrointestinal tract and is associated with systemic, extraintestinal, and atypical manifestations. Hemophagocytic lymphohistiocytosis (HLH), also known as macrophage activation syndrome, is a rare and severe inflammatory disorder that may occur secondary to infections, malignancies, or autoimmune diseases. Its association with CD is extremely uncommon. We report the case of an 8-year-old male who initially presented with nonspecific symptoms including lower limb pain, lumbalgia, and progressive abdominal pain, evolving into respiratory failure and cardiogenic shock, which required admission to the intensive care unit (ICU). He developed bicytopenia, persistent fever, rash, bilateral pleural effusion, hyperferritinemia, hypertriglyceridemia, and signs of systemic inflammation, raising clinical suspicion for HLH. Infectious and hematologic malignancies were ruled out. The patient received intravenous immunoglobulin, broad-spectrum antibiotics, antifungal agents, and immunomodulatory treatment. Gastrointestinal symptoms included melena-like diarrhea, hematochezia, abdominal distension, and elevated fecal calprotectin levels. Abdominal CT imaging showed colonic wall thickening and mesenteric lymphadenopathy. Esophagogastroduodenoscopy, colonoscopy, and histopathological analysis confirmed the diagnosis of CD. Treatment with infliximab was initiated, leading to a favorable clinical response. This case underscores an atypical presentation of CD associated with HLH, posing significant diagnostic and therapeutic challenges.